Simple surface treatments to modify protein adsorption and cell attachment properties within a poly(dimethylsiloxane) micro-bioreactor - Boxshall, K; Wu, M; Cui, Z; Cui, Z; Watts, J; Baker, M (2006)
Poly(dimethylsiloxane) (PDMS) elastomers are widely used in biological laboratories to produce prototype micro-bioreactors. The need was identified for a simple modification of the PDMS surface to prevent protein adsorption and cell attachment in certain areas and to increase the level of cell attachment where desirable. A study has been undertaken into the effect on protein adsorption and cell attachment of adsorbed surfactants and sodium hydroxide (NaOH) modification of the surface. The proteins are adsorbed from Dubecco's Modified Eagles Medium (DMEM) supplemented with foetal calf serum, HEPES, antibiotics, and ascorbic acid, as will be used to maintain the cells in the micro-bioreactor. Protein adsorption has been quantified by X-ray photoelectron spectroscopy (XPS) and the viable cell attachment by MTT assay. Protein and cell configuration were studied by atomic force microscopy (AFM) and light microscopy (LM) respectively. A positive correlation is observed between the level of protein adsorption and cell attachment. The Pluronic® F68 surfactant treatment exhibited the greatest reduction in protein adsorption and cell attachment, followed by the Pluronic® F127, with Tween™ 20 being the least effective. The NaOH treatment showed a substantial increase in both protein adsorption and cell attachment. Copyright © 2006 John Wiley and Sons, Ltd.